The design study for the development of sea wall construction on mangrove ecosystems : A case study of Tambak Lorok and Genuk district - Malasari Harahap; Sudarno Sudarno; Fuad Muhamad (Journal of Bioresources and Environmental Sciences, 2024)
The Design Study of the Semarang Sea Wall Development Plan will result in a change in environmental conditions in the eastern coastal area. Changes in environmental conditions that will occur in the area include changes in sea currents which originally flowed eastward moving to the Tambak Lorok area on the west coast and the Java Sea. The method uses Descriptive Qualitative with the help of SEM analysis. Based on the results of the analysis of the SEM model, it is known that the indicator that will be affected based on the Design Study of the Sea Wall Development Plan is the Mangrove Ecosystem of 0.477. To maintain the sustainability of the mangrove ecosystem, a coastal area management system needs to pay attention to the principle of the continuity of the function of existing mangrove forests. Mangrove ecosystems in coastal areas that are maintained, and supported by awareness and common perceptions of various parties about the importance of the existence of mangrove ecosystems will have an impact on the sustainability of coastal areas.